2019
DOI: 10.1089/thy.2018.0541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extranodal Extension on Risk Stratification in Papillary Thyroid Carcinoma

Abstract: Background: The current American Thyroid Association risk-stratification system for papillary thyroid carcinoma (PTC) incorporates the number and size of positive lymph nodes (LNs) but places less weight on extranodal extension (ENE). This study investigated how to incorporate ENE into the current system to predict recurrence better in PTC N1 patients. Methods: A total of 369 N1 PTC patients without distant metastasis were enrolled. The combination of number of positive LNs and LNs with ENE that had the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
11
1
1
Order By: Relevance
“…N1 PTC patients were divided into three groups according to the fraction of MLNs with ENE; ENE was a strong predictor, as shown in univariable and multivariable Cox proportional hazard models (highest HR). Since the presence of ENE might be closely related to the actual number of MLNs, the inclusion of ENE in the 2015 ATA RSS may be difficult (24,38). However, as demonstrated in this study, the use of appropriate statistical analyses to estimate the optimal number or proportion may enable the incorporation of ENE as a clinically useful predictor (24).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…N1 PTC patients were divided into three groups according to the fraction of MLNs with ENE; ENE was a strong predictor, as shown in univariable and multivariable Cox proportional hazard models (highest HR). Since the presence of ENE might be closely related to the actual number of MLNs, the inclusion of ENE in the 2015 ATA RSS may be difficult (24,38). However, as demonstrated in this study, the use of appropriate statistical analyses to estimate the optimal number or proportion may enable the incorporation of ENE as a clinically useful predictor (24).…”
Section: Discussionmentioning
confidence: 80%
“…Since the presence of ENE might be closely related to the actual number of MLNs, the inclusion of ENE in the 2015 ATA RSS may be difficult (24,38). However, as demonstrated in this study, the use of appropriate statistical analyses to estimate the optimal number or proportion may enable the incorporation of ENE as a clinically useful predictor (24). Despite the presence of several MLNs with DR, we selected and analyzed the most severe MLNs, which proved to be a prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following study limitations, conversely, should be considered: (1) Although other nodal characteristics, such as extra‐nodal extension 35 and metastatic LN size, 19 may carry prognostic information, it was not possible to retrieve data on these histologic details consistently in this retrospective study over a period of 10 years; (2) Various pathological subtypes (eg tall‐cell and columnar‐cell variants) were not considered in our analyses due to their extremely rare incidence; (3) We did not have genomic information on patients that might impact their competing risks of cancer persistence and recurrence. Recently, genetic markers have also been proposed as prognostic factors for paediatric DTC 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ENE is an important prognostic indicator in breast cancer and oral cancer. It has been previously suggested that a new risk stratification system incorporating ENE for predicting structural recurrent disease should be developed, but Shen et al questioned this (11,12). The prognostic role of ENE in PTC has long been controversial.…”
Section: Discussionmentioning
confidence: 99%